ESCALATION OF GLOBAL COMPETITIVENESS OF SONGKOK MSMES IN BUNGAH DISTRICT THROUGH ARTIFICIAL INTELLIGENCE (AI)-BASED DIGITAL MARKETING AND HALAL CERTIFICATION - Imam Nur Aziz; Muhammad Shohib; Mohammad Majduddin; Muhammad Najib; Fitriya Fauzi (SMARTINDO, 2025)
Bungah District is known as the center of the Songkok industry in Gresik Regency and has significant economic potential. However, the sustainability of this business faces serious challenges, including market stagnation due to low digital literacy and the absence of halal product assurance, which is now an absolute requirement for the global market. The inability to adapt to technology makes it difficult for local products to penetrate modern marketplaces. This community service program aims to enhance the global competitiveness of Songkok MSMEs by adopting Artificial Intelligence (AI) technology in marketing strategies and accelerating business legitimacy. The approach used is Community-Based Participatory Research (CBPR) integrated with the Participatory Learning and Action (PLA) method. This activity actively involved 30 Songkok artisans through stages of socialization, technical training in creating visual content with Canva AI, and assistance with registering SiHalal accounts. Program effectiveness was measured using comparative pre-test and post-test analysis. The results showed a significant increase in partners’ average understanding, rising from an initial score of 10% to 82.5% post-intervention. In addition to improving cognitive competence, this activity successfully produced tangible outputs, including 28 AI-based professional digital catalog designs, 30 active social media business accounts, and 30 draft documents for halal certification submissions under the self-declare scheme. The program concludes that integrating efficient AI technology with compliance with Sharia regulations effectively increases partners' self-efficacy to transform from traditional markets into a competitive, sustainable export ecosystem.